Local Wisdom-Based Arabic Speaking Instruction and Student Achievement in Indonesian Madrasah - Maslahatul Hidayah; Ahmad Rifa’i; Hamida Gadoum (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
Despite extensive research on Arabic-speaking skills, the integration of local wisdom into structured, performance-based learning strategies in madrasahs remains underexplored. This study aims to describe the implementation of local wisdom-based maharah kalam strategies and analyze their impact on student achievement. A qualitative case study approach was employed, involving observations, interviews with program coordinators, teachers, and students, as well as document analysis at MTsN 3 Jombang. The findings reveal that integrating local wisdom through direct instruction, repetitive drills, and collaborative learning significantly enhances students' speaking proficiency in both formal and informal Arabic contexts, including khitobah, storytelling, news reading, and poetry recitation. Teacher competence and personalized mentoring further boosted student confidence. Thirteen district and provincial awards evidence these outcomes. The study concludes that local wisdom-based strategies not only improve linguistic competence but also foster measurable academic achievement, and recommends their adoption in similar madrasah contexts to create more contextually meaningful, competitive Arabic language learning environments. Meskipun penelitian tentang keterampilan berbicara bahasa Arab sudah banyak dilakukan, integrasi kearifan lokal ke dalam strategi pembelajaran berbasis kinerja yang terstruktur di madrasah masih jarang dieksplorasi. Penelitian ini bertujuan untuk mendeskripsikan implementasi strategi pembelajaran maharah kalam berbasis kearifan lokal dan menganalisis dampaknya terhadap prestasi siswa. Pendekatan kualitatif dengan desain studi kasus digunakan, meliputi observasi, wawancara dengan koordinator program, guru, dan siswa, serta analisis dokumen di MTsN 3 Jombang. Temuan menunjukkan bahwa integrasi kearifan lokal melalui instruksi langsung, latihan berulang, dan pembelajaran kolaboratif secara signifikan meningkatkan kemampuan berbicara siswa dalam bahasa Arab formal dan informal, termasuk khitobah, bercerita, membaca berita, dan pembacaan puisi. Kompetensi guru dan bimbingan personal juga meningkatkan kepercayaan diri siswa. Hasil ini dibuktikan dengan perolehan tiga belas penghargaan tingkat kabupaten dan provinsi. Penelitian menyimpulkan bahwa strategi berbasis kearifan lokal tidak hanya meningkatkan kompetensi linguistik tetapi juga prestasi akademik terukur, serta merekomendasikan adopsinya di konteks madrasah serupa.